PENGARUH KOMITMEN, MOTIVASI, KOMPLEKSITAS TUGAS DAN BUDAYA SUPORTIF TERHADAP KEPUASAN KERJA - ARYA PRADIPTA (Media Bisnis, 2013)
The objective of this study is to get an empirically evidence about the affecting factors of auditor’s job satisfaction. The factors affecting are organizational commitment, professionalism commitment, motivation, task complexity, and supportive culture.Data collected through questionnaires. There 180 quesstionnaires distributed to 17 registered public accountant in DKI Jakarta as respondents. Ninety six used questionnaires used for the analysis. This data analysis was done by using multiple regression.The result of this research showed that organizational commitment, professionalism commitment, motivation, task complexity and supportive culture have effect toward auditor’s job satisfaction.